PENERAPAN KOMBINASI METODE SAW DAN TOPSIS DALAM MENENTUKAN DOMPET DIGITAL TERBAIK (STUDI KASUS: KOTA SURABAYA) - Siti Nur Fadilah; Raden Sulaiman (Universitas Negeri Surabaya, 2023)
Currently, various types of digital wallets are present in society with various advantages and facilities offered. This is in line with life in the digital era, where the increasing use of digital wallets is in every daily activity, especially in Surabaya. However, the existence of a variety of digital wallet choices can cause a problem, where people can have difficulty considering the selection of the best digital wallet that will be used in their daily lives. So to overcome these problems, it is necessary to conduct a study that aims to identify which digital wallet is the best in the Surabaya city area in the hope that it can help and provide recommendations to the wider society, especially the people of Surabaya in determining the best digital wallet. The criteria used in this study are convenience, promotion, security, service features, and benefits. The alternatives used in this study are GoPay, DANA, OVO, ShopeePay, and LinkAja. The decisionmaking method applied in this study is a combination of the SAW and the TOPSIS method. The stage begins by applying the SAW method which produces a normalized matrix R, then continued by applying the TOPSIS method to obtain alternative ranking. The results of this study show that ShopeePay is the best digital wallet with the highest preference value of 0.997, followed by other digital wallets namely OVO, GoPay, DANA and LinkAja.